Dormência de sementes em germoplasma de aveia-preta - Kehl, Kassiana (2021)
Black oats are one of the most cultivated winter cereals in the south of Brazil for their forage aptitude and benefits when used for soil cover. Its seeds have dormancy and when ill - managed during grazing, desiccation and harvesting practices, it favors the formation of seed banks, ensuring the perpetuation of the species throughout the seasons. The characterization of genotypes that express variability in seed dormancy can provide breeder with selection options. The possibility of predicting the viability of seeds that are deposited in the soil can assist in the adoption of appropriate management practices so that the species does not become difficult to control. The objective of the work was to evaluate the dormancy of black oat seeds in different approaches, which comprised three studies carried out between 2018 and 2020. In the first study the objective was evaluate if there is an effect of natural reseeding of black oat genotypes in wheat and white oat seeds fields production. In the second study the objective was characterize 30 black oat genotypes regarding seed dormancy. Finally, the third aimed to verify whether there is a temporal effect on the expression of dormancy of seeds of black oat genotypes in the soil, under burial, under field conditions. The results showed that the natural reseeding of black oat genotypes was attenuated from one year to another, the control (area cultivated with white oats in 2017) was the treatment that did not present black oat plants during the development of wheat and of white oats. The reseeding of black oats negatively interferes with the production of wheat and white oat seeds and it differs between genotypes. In wheat the reseeding of black oats was more pronounced than in white oats. There is variability by the germination test for dormant seeds among the black oat genotypes and this is overcome from 60 days after harvest.The genotypes with the highest dormancy percentages are IAPAR61-Ibiporã and ALPHA 1629. The black oat genotypes show similar behavior regarding the survival and viability of seeds in the soil. Black oat seeds remain viable in the soil for a period of 450 days after burial. In order to contribute to advances in genetic improvement, it is suggested to conduct studies with the objective of verifying the relation between the seed dormancy character and forage aptitude and coverage of black oat genotypes.